조직몰입, 시장지향성, 조직학습의 관계에 관한 실증연구 - 김대업; Dae Up Kim; 정기한; Ki Han Chung (Journal of global scholars of marketing science, 2002)
A Study on the Relationship between organizational commitment, market orientation and organizational learning KCI Citation Count: 9